Kombinasi Damerau Levenshtein dan Jaro-Winkler Distance Untuk Koreksi Kata Bahasa Inggris - Bonifacius Vicky Indriyono (Maranatha University Press, 2020)
Writing is one of the efforts made by the writer to express ideas and ideas to others. But sometimes when writing, there are many errors in typing spelling, especially English spelling, resulting in errors in capturing the meaning and meaning of the writing. To overcome this problem, we need a system that can detect word spelling errors. Damerau Levenshtein and Jaro Winkler Distance Algorithms are algorithms that can be used as a solution to detect English typing errors. From the test results, it can be concluded that the Damerau Levenshtein and Jaro-Winkler Distance are able to optimally detect word mismatches and look for similarities of words compared. The Damerau Levenshtein Distance works by finding the smallest distance value, while the Jaro-Winkler Distance works by finding the greatest proximity value of the string being compared. Using this algorithm, errors in writing the spelling of words can be minimized. Keywords— Algorithm; Damerau Levenshtein; Jaro Winkler; Spelling Cheker; String Matching.